Geochemical characteristics and structural features of the LCT pegmatites in Potoskavaara, Kitee-Tohmajärvi pegmatite province - Pääkkönen, Kirsi (My University, 2025)
The demand for battery materials such as lithium, cobalt and graphite are increasing with the green transition towards more sustainable energy sources. Lithium plays a particularly important role in the development of energy storage, electric vehicles, with LCT (Lithium-Cesium-Tantalum) pegmatite deposits being an important source for these critical metals. Several heterogeneous and Svecofennian LCT pegmatite dykes have been discovered in the 200 km² wide area of the Kitee-Tohmajärvi pegmatite province, with the most prominent Li-dykes located in the northern parts of the Potoskavaara area. The aim of this study is to find the compositional differences and variations in fertility of the pegmatite dykes in the Potoskavaara. The study additionally provides regional information to better understand the formation of the pegmatite dykes in the area. The elemental results indicate that the Potoskavaara dykes represent peraluminous S-type fertile pegmatites, which are characterized by elevated concentrations of rare metals, along with A/CNK >1.1, Mg/Li <10, and Nb/Ta <8 ratios. Furthermore, they display high Al, low Ca, Fe, and Mg concentrations, and varying K and Na contents. The pegmatite dykes exhibit both geochemical and mineralogical compositional differences, with enrichment in rare elements such as Be >Cs >Rb >Nb ≥Ta >Li >Sn as fractionation progresses. Elemental enrichment supports the hypothesis of regional zonation, which enables the classification of the area's pegmatites into four fertile rock types: the most evolved RE-pegmatites, potassic pegmatites, sodic aplites, and the most common pegmatitic leucogranites. Signs of hydrothermal events are evident in pegmatite dykes, as mineral inclusions, compositional, and textural changes. In conjunction with the geochemical results, these observations suggest that the enrichment of the pegmatites with rare metals is a result of both magmatic and hydrothermal processes. Alongside fractional crystallization, the partial melting of surrounding rocks may have affected the formation. The most evolved pegmatites are found in the northern parts of the Potoskavaara area approximately 10 km from the so-called Kitee granite intrusion. The source of the Li-pegmatites is likely the Kitee granite, although further relative age dating is needed to confirm this. The multiple deformation phases of different ages have occurred in the area, which complicates the interpretation of the original source of the pegmatite dykes. The enrichment of rare elements in the surrounding rock could potentially lead to the discovery of undiscovered Li-pegmatite dykes in the area and guiding future mineral exploration efforts.

Akkumateriaalien, kuten litiumin, koboltin ja grafiitin kysyntä kasvaa vihreän siirtymän myötä kohti kestävämpiä energialähteitä. Erityisesti litiumilla on merkittävä rooli energian varastoinnin ja sähköajoneuvojen kehittymisessä. Näiden kasvavien tarpeiden vuoksi LCT (Litium-Cesium-Tantaali)-pegmatiittiesiintymät ovat tärkeitä lähteitä kriittisille metalleille. Kiteen-Tohmajärven 200 km2 laajuiselta pegmatiittiprovinssin alueelta on löydetty useita heterogeenisiä ja Svekofennisia LCT-pegmatiittijuonia, joista Li-rikkaimmat juonet sijaitsevat Potoskavaaran alueella. Tämän tutkimuksen tavoitteena on osoittaa Potoskavaaran alueen pegmatiittijuonten koostumuserot ja vaihtelut niiden fertiilisyydessä. Lisäksi tutkimus laajentaa ymmärrystä alueen pegmatiittien muodostumisesta ja lähdegranitoidista. Tulokset osoittavat, että Potoskavaaran juonet edustavat peralumiinisia S-tyypin fertiilejä pegmatiittijuonia, joille on tyypillistä kohonneet harvinaisten metallien pitoisuudet sekä A/CNK >1.1, Mg/Li <10 ja Nb/Ta <8. Lisäksi niille on ominaista korkea Al-pitoisuus, matalat Ca-, Fe- ja Mg-pitoisuudet, sekä vaihtelevat K- ja Na-pitoisuudet. Pegmatiittijuonissa on sekä geokemiallisia että mineralogisia koostumuseroja, jotka ilmenevät harvinaisten alkuaineiden Be >Cs >Rb >Nb ≥Ta >Li >Sn rikastumisella fraktioitumisen kehittyessä. Alkuaineiden rikastumistrendit tukevat hypoteesia alueellisesta vyöhykkeellisyydestä, joka mahdollistaa alueen pegmatiittien luokittelun neljään kivilajiryhmään: kehittyneimpiin RE-pegmatiitteihin, kalipegmatiitteihin, natriumapliitteihin sekä kaikista yleisimpiin pegmatiittisiin leukograniitteihin. Pegmatiittijuonissa on hydrotermisten tapahtumien merkkejä, kuten mineraalisulkeumia, koostumus- sekä tekstuurimuutoksia. Geokemiallisten tulosten kanssa nämä havainnot viittaavat siihen, että pegmatiittijuonten rikastuminen harvinaisilla metalleilla on seurausta sekä magmaattisista että hydrotermisistä prosesseista. Fraktioitumisen kiteytymisen lisäksi muodostumiseen on saattanut vaikuttaa ympäröivän isäntäkiven osittaissulaminen. Kaikista kehittyneimmät pegmatiitit sijoittuvat Potoskavaaran alueen pohjoisosiin rakenteellisesti monimutkaistelle ja litologisesti vaihtelevalle alueelle, noin 10 km päähän Kiteen graniitista. Tuloksien perusteella Li-pegmatiittien lähde on Kiteen graniitti, mutta tarkempia iänmäärityksiä tarvitaan tämän varmistamiseksi. Tutkimusalueen rakenteelliset piirteet viittaavat kuitenkin siihen, että alueella on vaikuttanut useita eri-ikäisiä deformaatiovaiheita, jotka vaikeuttavat pegmatiittien alkuperäisen lähteen tulkintaa. Harvinaisten alkuaineiden mahdollinen rikastuminen ympäröivään isäntäkiveen voisi mahdollisesti ohjata malminetsintää alueen vielä paljastumattomien Li-pegmatiittijuonien löytämiseksi.
Keywords: LCT-pegmatite, lithium, fertility, source, zonation, exploration, LCT-pegmatiitti, litium, fertiilisyys, lähde, vyöhykkeellisyys, malminetsintä